Need Analysis on The Inclusive English Materials for The Primary Graders: Voices from Practitioners - Mu'alimin Mu'alimin; Khoiriyah Khoiriyah; Devi Mariatul Qiptiah (Madrosatuna: Journal of Islamic Elementary School, 2019)
This study is aimed at conducting a need analysis on the existence of English materials for the students of elementary level in an inclusive classroom. The data is obtained from inclusive teacher who has ELT undergraduate educational background and the students of pre-service training of PGMI at IAIN Jember. The result shows that teacher takes a very important role in conducting an inclusive classroom in primary level due to the fact that they have to prepare materials and activities specifically for the students who have social, emotional, and behavioral difficulties (SEBD). Listening and speaking skill (oracy cycle) are considered as the first skills to be taught and introduced to the students of primary level in order to be able to make interrelationship with others more easily. English materials that compatible with the students of primary level in an inclusive classroom are the materials that encourage their multiple intelligences and recognize their learning style. The teaching procedure is emphasized on the role play in the form of guided instruction flowing from fully guided, partly guided, to fully free learning so the scaffolding of presenting materials which emphasized on touching their feeling can improve their sense of empathy and sense of taking care of others as well as building their social skill.